2017
DOI: 10.1167/iovs.16-21311
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Characters and Localization of Images Using Direct Multiple-Electrode Stimulation With a Suprachoroidal Retinal Prosthesis

Abstract: Citation: Shivdasani MN, Sinclair NC, Gillespie LN, et al.; for the Bionic Vision Australia Consortium. Identification of characters and localization of images using direct multiple-electrode stimulation with a suprachoroidal retinal prosthesis. Invest Ophthalmol Vis Sci. 2017;58:3962-3974. DOI: 10.1167/iovs.16-21311 PURPOSE. Retinal prostheses provide vision to blind patients by eliciting phosphenes through electrical stimulation. This study explored whether character identification and image localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 25 publications
(61 reference statements)
1
25
0
Order By: Relevance
“…We have previously found that suprachoroidal implant recipients made significant eye movements in response to stimuli during a static image localization task, despite being instructed not to. 16 A separate study in Argus II recipients found that camera-gaze misalignments occurred frequently during a visual search task, often due to the vestibulo-ocular reflexive movements that occur naturally during head scanning, and that patients rely on a series of complex head movements to properly localize objects in daily life. 8 Some have suggested that percept localization is so difficult that many patients simply use their devices as light detectors, ignoring any retinotopic information and instead relying solely on head and neck orientation.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously found that suprachoroidal implant recipients made significant eye movements in response to stimuli during a static image localization task, despite being instructed not to. 16 A separate study in Argus II recipients found that camera-gaze misalignments occurred frequently during a visual search task, often due to the vestibulo-ocular reflexive movements that occur naturally during head scanning, and that patients rely on a series of complex head movements to properly localize objects in daily life. 8 Some have suggested that percept localization is so difficult that many patients simply use their devices as light detectors, ignoring any retinotopic information and instead relying solely on head and neck orientation.…”
Section: Introductionmentioning
confidence: 99%
“…72,75 In a series of psychophysical tasks delivered by direct electrode stimulation, two of the subjects demonstrated better than chance character recognition and static object localization, while one was able to detect dynamic image trajectory. 76 At the time of explantation, electrical stimulation was still possible, although it was noted in all cases that a fibrous capsule had developed around the implant. 77…”
Section: Suprachoroidal Prosthesesmentioning
confidence: 99%
“…9,10 Large electrodes (necessitated by safe charge density limits), current spread, and the incidental stimulation of axonal pathways lead to large and irregularly shaped phosphenes and limited spatial discriminability. [11][12][13] Additionally, non-selective stimulation that activates both "on" and "off" pathways indiscriminantly is likely to have unusual perceptual effects that are not well understood. 14 Novel electrode designs and advances in targeted stimulation strategies offer some promise for future visual prostheses.…”
Section: Introductionmentioning
confidence: 99%
“…9,13,19,20 In addition to spatial and form vision, visual prostheses should also ideally enable the perception of motion. Discrimination of direction of motion has previously been demonstrated in patients implanted with a 24-channel suprachoroidal retinal implant, 13 a subretinal implant, 9,20 and an epiretinal implant. 21 The subjective characteristics of the percepts experienced by participants during these tasks, as well as the particular perceptual cues used to identify motion, has received little attention.…”
Section: Introductionmentioning
confidence: 99%